Penentuan Waktu Pengasinan Telur Bebek yang Optimal Berdasarkan Pengukuran Sifat Fisik dan Kelistrikan dengan Pendekatan Response Surface Methodology (RSM) - Elza Dina (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to determine the optimal time of duck egg salting using Response Surface Methodology (RSM) based on physical properties (RH and pH) and electrical properties (capacitance and conductivity). Secondary data from Firdhaus' (2019) research was analyzed using Minitab software. The results showed that the optimal salting time was 11.50 days. In this condition, RH reached 45.7950%, egg white pH was 7.550, egg yolk pH was 6.360, egg white capacitance was 146.920 F, egg yolk capacitance was 100.280 F, egg white electrical conductivity was 25.8050 𝛺𝑚−1 , and egg yolk electrical conductivity was 2.360 𝛺𝑚−1 . This study shows that physical and electrical properties play an important role in the salting process, providing guidance for optimizing the quality and shelf life of salted eggs.
FINALISASI oleh Arif 2026 Mei 19
Keywords: Salted egg; salting time; Response Surface Methodology (RSM); physical properties; electrical properties.